2018
DOI: 10.1097/md.0000000000011367
|View full text |Cite
|
Sign up to set email alerts
|

Association between use of aspirin or non-aspirin non-steroidal anti-inflammatory drugs and erectile dysfunction

Abstract: Objective:There are various etiologies of erectile dysfunction (ED), including endothelial dysfunction, atherosclerosis, and chronic inflammation. Aspirin has a protective role against endothelial dysfunction and atherosclerosis, whease all non-steroidal anti-inflammatory drugs (NSAIDs) are known for their anti-inflammatory properties. However, association between the use of aspirin or non-aspirin NSAIDs and ED is controversial. Therefore, we reviewed this relationship.Methods:We systematically reviewed the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…The constant NOS-NO-cGMP pathways were in accordance with ICP, AUC, and ICP/MAP indices, which verified that long-term aspirin administration had beneficial effects on erectile function. This was also consistent with previous clinical studies 2,3,18,39,40 .…”
Section: Discussionsupporting
confidence: 93%
“…The constant NOS-NO-cGMP pathways were in accordance with ICP, AUC, and ICP/MAP indices, which verified that long-term aspirin administration had beneficial effects on erectile function. This was also consistent with previous clinical studies 2,3,18,39,40 .…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, it might have a chance to be effective in reducing erectile dysfunction. Low-grade inflammation and high circulating pro-inflammatory markers occur during the vascular erectile dysfunction process . Maca may benefit the anti-inflammatory related diseases.…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review reported contrasting results regarding the association between Aspirin and ED. [ 32 ] Some studies have identified a protective association of Aspirin by preserving impairment nitric oxide synthase and reducing hypercoagulability of blood flow in penile organs. On the other hand, a few studies concluded Aspirin as a risk factor because of their interference in the production of prostaglandin.…”
Section: Discussionmentioning
confidence: 99%